2020
DOI: 10.3390/diagnostics10110968
|View full text |Cite
|
Sign up to set email alerts
|

Iron Rims as an Imaging Biomarker in MS: A Systematic Mapping Review

Abstract: Background: Multiple sclerosis (MS) is an autoimmune, inflammatory, demyelinating and degenerative disease of the central nervous system (CNS). To date, there is no definitive imaging biomarker for diagnosing MS. The current diagnostic criteria are mainly based on clinical relapses supported by the presence of white matter lesions (WMLs) on MRI. However, misdiagnosis of MS is still a significant clinical problem. The paramagnetic, iron rims (IRs) around white matter lesions have been proposed to be an imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 67 publications
2
22
0
Order By: Relevance
“…Examining periventricular lesions of similar size revealed a high degree of correlation between reduction of the rate of lesion expansion and increasing distance from CSF, while grouped analysis of individual lesions demonstrated a significantly higher proportion of expanding lesions in close proximity to the ventricles compared to the deep white matter. While earlier work has indicated that the anatomical distribution of expanding lesions follows the common periventricular pattern of lesion distribution in MS, 2,16 this study is the first to demonstrate a direct relationship between the degree of chronic lesion expansion and the distance from the ventricular border, highlighting CSF-related dependency of the chronic inflammatory process. Providing that lesion expansion is an imaging equivalent of slow-burning inflammation at the lesion rim, our results suggest that inflammatory activity at the rim of chronic lesions is also dependent on the distance from CSF.…”
Section: Discussionmentioning
confidence: 41%
“…Examining periventricular lesions of similar size revealed a high degree of correlation between reduction of the rate of lesion expansion and increasing distance from CSF, while grouped analysis of individual lesions demonstrated a significantly higher proportion of expanding lesions in close proximity to the ventricles compared to the deep white matter. While earlier work has indicated that the anatomical distribution of expanding lesions follows the common periventricular pattern of lesion distribution in MS, 2,16 this study is the first to demonstrate a direct relationship between the degree of chronic lesion expansion and the distance from the ventricular border, highlighting CSF-related dependency of the chronic inflammatory process. Providing that lesion expansion is an imaging equivalent of slow-burning inflammation at the lesion rim, our results suggest that inflammatory activity at the rim of chronic lesions is also dependent on the distance from CSF.…”
Section: Discussionmentioning
confidence: 41%
“…26,27 However, there are reservations on the clinical utility as PRLs are only seen in a minority of WMLs. 13,28 This retrospective international, multicentre study within the Magnetic Resonance Imaging in MS (MAGNIMS) Study Group aimed to test the potential for PRLs in clinical practice. MRIs for patients with MS and MS mimics (including cerebral small vessel disease, migraine and NMOSD) were compared.…”
Section: Paramagnetic Rims Are a Promising Diagnostic Imaging Biomark...mentioning
confidence: 99%
“…Examining periventricular lesions of similar size revealed a high degree of correlation between reduction of the rate of lesion expansion and increasing distance from CSF, while grouped analysis of individual lesions demonstrated a significantly higher proportion of expanding lesions in close proximity to the ventricles compared to the deep WM. While earlier work has indicated that the anatomical distribution of expanding lesions follows the common periventricular pattern of lesion distribution in MS, 2,18 this study is the first to demonstrate a direct relationship between the degree of chronic lesion expansion and the distance from the ventricular border, highlighting CSFrelated dependency of the chronic inflammatory process. Providing that lesion expansion is an imaging equivalent of slow-burning inflammation at the lesion rim, our results suggest that inflammatory activity at the rim of chronic lesions is also dependent on the distance from CSF.…”
Section: Periventricular Gradient Of Expansion and Severity In Chroni...mentioning
confidence: 42%